Indirect impacts of commercial gold mining on adjacent ecosystems. (November 2022) - Seki, Hamidu A.; Thorn, Jessica P.R.; Platts, Philip J.; Shirima, Deo D.; Marchant, Rob A.; Abeid, Yahya; Baker, Neil; Annandale, Mark; Marshall, Andrew R.
Abstract: Mining is important for economic development in many tropical countries, but mining can have serious impacts on biodiversity, both directly through operations at extraction sites, and indirectly via wider social-economic development. However, mitigation efforts by large-scale mining operators focus almost exclusively on extraction sites. We provide a rare assessment of mining impacts on vegetation structure and biodiversity with increasing distance from three commercial gold mines of varying ages in Tanzania (0 years, 8 years, and 19 years since establishment). We show that mining is associated with impacts that manifest largely outside operational lease boundaries. At the two older mine sites, aboveground carbon and tree stem density are significantly higher within lease boundaries compared to outside, while there is no such effect at the new site. Further, tree stem density, aboveground carbon, and tree and butterfly species richness all decrease with increasing distance from extraction sites, with these effects again increasing with mine age. Frugivorous bird species richness is lower outside older mines, while abundance declines in frugivorous and granivorous birds are associated with declines in tree stem density, which may have implications for forest regeneration. These impacts result from new and expanding settlements around mining concessions between 2000 and 2019 and associated demand for timber and fuelwood. We recommend rigorous, integrated impact assessments and conservation planning in mining landscapes, to pre-empt the development of settlements and secondary industries around mining sites and so balance outcomes across the mining sector, natural resource-based and other livelihoods, and conservation agendas. Highlights: Commercial gold mining impacts on adjacent ecosystems accumulate with age and distance from the mine. Ecosystems adjacent to mines have reduced carbon stocks and altered tree, butterfly, and bird species communities. These impacts of mining accrue indirectly via in-migration and socio-economic development. Integrated land use planning can improve sustainable development in mining regions.